2014
DOI: 10.1016/j.jmb.2014.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Transient Contacts on the Exterior of the HK97 Procapsid That Are Essential for Capsid Assembly

Abstract: The G-loop is a 10-residue glycine-rich loop that protrudes from the surface of the mature bacteriophage HK97 capsid at the C-terminal end of the long backbone helix of major capsid protein subunits. The G-loop is essential for assembly, is conserved in related capsid and encapsulin proteins, and plays its role during HK97 capsid assembly by making crucial contacts between the hill-like hexamers and pentamers in precursor proheads. These contacts are not preserved in the flattened capsomers of the mature capsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 75 publications
(120 reference statements)
1
36
0
Order By: Relevance
“…Recently, the coat protein of HK97 and related phages was shown to have a glycine rich “G-loop” that also reaches across capsomers to interact with the E-loop of an adjacent subunit. Unlike the flexible D-loop in P22’s coat protein, the HK97 G-loop appears to be rigid and is proposed to limit subunit conformational flexibility during capsomer assembly (Tso et al, 2014). The role of the D-loop in P22 procapsid assembly is not well defined and is being investigated currently.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the coat protein of HK97 and related phages was shown to have a glycine rich “G-loop” that also reaches across capsomers to interact with the E-loop of an adjacent subunit. Unlike the flexible D-loop in P22’s coat protein, the HK97 G-loop appears to be rigid and is proposed to limit subunit conformational flexibility during capsomer assembly (Tso et al, 2014). The role of the D-loop in P22 procapsid assembly is not well defined and is being investigated currently.…”
Section: Discussionmentioning
confidence: 99%
“…SDS-polyacrylamide gels (Figure 3B) confirmed that the bulk of the major capsid protein from the four mutants was in the pellet fractions, where it was present as 42 kDa monomers and as ladders of crosslinked 42 kDa monomers. In normal HK97 assembly, crosslinking only occurs as a late step as Prohead II expands to become Head II [21], well after cleavage of the major capsid protein to 31kDa (Figure 1A), so the presence of crosslinked 42 kDa protein ladders, as observed here, usually indicates that abnormal assembly has occurred [4]. Accordingly, we examined the pellet fractions of the E153 mutants by electron microscopy.…”
Section: Resultsmentioning
confidence: 98%
“…Under these conditions, expression of HK97 capsid components is so efficient, that they can be readily analyzed by electrophoresis of unpurified extracts [4, 22]. To aid in the interpretation of these experiments, we included mutant K92A as a control that yields a wide spectrum of HK97 assembly intermediates to serve as markers for proheads, heads and capsomers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations